Effect of guided imagery on the functional rehabilitation of knee injured soccer players - Rahnama, N.; Khayam-Bashi, K.; Rostami Haji-Abdi, M. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Guided imagery is a psychosomatic treat that uses of narrative and story for their effects on mental images and patterns. Guided imagery is a complementary therapy that maybe guided by a physician, a sound or video recording or by the same person. The purpose of this study was to determine the effect of guided imagery on functional rehabilitation of knee injured male soccer players. Methods Altogether 10 athletes with a knee injury were selected and randomly divided into experimental (N= 5, age= 26.40±4.21 year) and control (N= 5, age= 28.17±8.54 year) groups. Experimental and control group athletes after anterior cruciate ligament or meniscus surgery were gradually entered into research. In addition to physiotherapy exercises, subjects in experimental group received guided imagery exercises daily for 4 weeks. Range of motion were measured in pre and post test by goniometer and maximum strength of extensor and flexor muscles and also proprioceptive error rate of knees were measured in pre and post tests by Biodex system 3. Data was analysed using Independent T test by SPSS 15. Results & Discussion Results of this study showed that guided imagery accompanied by physiotherapy such as physiotherapy alone, increased range of motion in the injured knees (11.33% & 9.2 % respectively) but differences was not significant (P>0.05). Regarding extensor muscles strength, an increase was observed in the experimental group (26.97%), but for the control group non significant decline was observed (P>0.05). For injured knee flexors muscle, increase in the experimental and control groups was observed (13.33% & 14.65% respectively), but this differences were not statistically significant (P>0.05). Proprioceptive errors rate in the injured knees in experimental groups decreased (9.97%) more compared to the control group (3.56%) but the difference was not statistically significant (P>0.05). Conclusion It can be concluded that guided imagery along with physiotherapy can be recommended for knee injured soccer players as they lead to an improvement (non significant) in selected factors such as range of motion, muscle strength and proprioception.